Euthanasia as privileged compassion - Buijsen, M. A. J. M., 1963- (Cambridge University Press, 2024)
This Element overviews developments and issues in Dutch euthanasia practice. Following an outline of the history of the Dutch Euthanasia Act and a survey of the most critical trends and figures, some current issues are explored in depth: euthanasia and incompetency, euthanasia by nonphysicians, and euthanasia for those who consider their lives completed. This Element is intended for a general readership, including undergraduate students in law, medicine, or ethics. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 17 May 2024).
Keywords: Euthanasia -- Netherlands -- History.; Euthanasia -- Law and legislation -- Netherlands.